Field aligned flows driven by neutral puffing at MAST. (6th April 2018) - Waters, I.; Frerichs, H.; Silburn, S.; Feng, Y.; Harrison, J.; Kirk, A.; Schmitz, O.
Abstract: Neutral deuterium gas puffing at the high field side of the mega ampere spherical tokamak (MAST) is shown to drive carbon impurity flows that are aligned with the trajectory of the magnetic field lines in the plasma scrape-off-layer. These impurity flows were directly imaged with emissions from C 2+ ions at MAST by coherence imaging spectroscopy and were qualitatively reproduced in deuterium plasmas by modeling with the EMC3-EIRENE plasma edge fluid and kinetic neutral transport code. A reduced one-dimensional momentum and particle balance shows that a localized increase in the static plasma pressure in front of the neutral gas puff yields an acceleration of the plasma due to local ionization. Perpendicular particle transport yields a decay from which a parallel length scale can be determined. Parameter scans in EMC3-EIRENE were carried out to determine the sensitivity of the deuterium plasma flow phenomena to local fueling and diffusion parameters and it is found that these flows robustly form across a wide variety of plasma conditions. Finally, efforts to couple this behavior in the background plasma directly to the impurity flows observed experimentally in MAST using a trace impurity model are discussed. These results provide insight into the fueling and exhaust features at this pivotal point of the radial and parallel particle flux balance, which is a major part of the plasma fueling and exhaust characteristics in a magnetically confined fusion device.